Coating modified high-nickel ternary positive electrode material, preparation method thereof and battery
By using the sol-gel method to coat barium zirconate on the surface of high-nickel ternary positive electrode material, the structural degradation and electrochemical performance degradation of the material under high voltage and high temperature conditions are solved, and higher cycle life and safety are achieved.
Patent Information
- Application Number
- CN202411782275.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-25
AI Technical Summary
High nickel ternary cathode materials have problems with cycle stability, thermal stability and compatibility with electrolytes, especially under high voltage and high temperature conditions, resulting in structural decay, capacity loss and shortened battery life.
The surface of the high-nickel ternary positive electrode material is coated with barium zirconate on the surface of the high-nickel ternary positive electrode material by the sol-gel method to form a uniform and dense barium zirconate layer, improving the structural stability and electrochemical properties of the material.
It significantly improves the structural stability and thermal stability of the material, reduces the reaction with the electrolyte, extends the cycle life of the battery and improves its safety.
Smart Images

Figure CN119695096A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a coated modified high-nickel ternary positive electrode material and a preparation method thereof, and a battery. Background Art
[0002] New energy vehicles have become an important part of the transformation of the energy system. As the power storage and supply of electric vehicles, lithium-ion batteries affect the power performance of electric vehicles and determine the endurance and service life of electric vehicles. The important factor affecting the performance of lithium-ion batteries is the positive electrode material. Ternary lithium-ion batteries use nickel cobalt manganese oxide as the positive electrode material, which has a higher energy density than traditional lithium cobalt oxide or lithium iron phosphate positive electrode materials. This allows the battery to store more electrical energy, thereby providing a longer range and longer service life.
[0003] High-nickel ternary cathode materials are an important type of ternary materials. However, high-nickel ternary cathode materials face some technical challenges in practical applications, such as poor cycle stability, insufficient thermal stability and compatibility issues with electrolytes. Especially under high voltage and high temperature conditions, these materials are prone to structural decay, resulting in capacity loss and shortened battery life. Stress degradation caused by local heat accumulation and anisotropic lattice strain poses a great obstacle to their widespread application. During the cycle process, anisotropic lattice changes lead to severe stress accumulation, resulting in microcracks along grain boundaries and severe particle crushing, which inevitably aggravates the attenuation of electrochemical performance, irreversible phase changes and harmful interfacial side reactions.
[0004] In response to these problems, common modification methods mainly include element doping, surface coating and construction of special structures, among which surface coating modification is widely used due to its advantages such as low cost and high controllability. Surface treatment of high-nickel positive electrode materials can improve the surface stability of positive electrode materials and effectively inhibit the side reactions between high-energy positive electrodes and organic electrolytes, becoming an important strategy and reliable way to regulate the surface interface of positive electrode materials. However, these surface treatments have limited effect on improving the life of the battery. Summary of the invention
[0005] The invention provides a coated modified high-nickel ternary positive electrode material and a preparation method thereof, and a lithium ion battery, so as to improve the cycle life of the lithium ion battery.
[0006] To solve the above problems, the technical solution provided by the present invention is as follows:
[0007] A method for preparing a coated modified high-nickel ternary positive electrode material comprises the following steps:
[0008] 1) mixing a soluble zirconium source and a soluble barium source uniformly in water, then adjusting the pH to 3-7, and stirring at 60-80° C. to obtain a sol;
[0009] 2) The ternary positive electrode material is mixed evenly with the sol prepared in step 1), heated in an inert atmosphere to evaporate the solvent, vacuum dried, and then sintered at 300-900° C. for 2-6 hours to obtain the product.
[0010] In step 1), the soluble zirconium source is at least one of zirconium chloride, zirconium acetate, zirconium nitrate and zirconium oxide.
[0011] In step 1), the soluble barium source is at least one of barium chloride, barium acetate, barium nitrate and barium oxide.
[0012] The molar ratio of the soluble zirconium source to the soluble barium source in step 1) is 1:1-3.
[0013] In step 2), the temperature for heating and evaporating the solvent is 50-150° C. and the time is 6-12 hours.
[0014] In step 2), the sintering temperature is preferably 500-600° C. The sintering time is preferably 5-6 hours.
[0015] The ternary positive electrode material is prepared by a method comprising the following steps: uniformly mixing nickel sulfate, cobalt sulfate and manganese sulfate in water, adding sodium hydroxide and ammonia water, stirring for reaction, solid-liquid separation, washing, and vacuum drying for 12-24 hours to prepare a precursor; then heat treating the precursor at 450-500° C. for 4-6 hours in an oxygen atmosphere; and then sintering at 700-800° C. for 12-18 hours.
[0016] The structure of the ternary cathode material can be expressed as LiNi x Co y Mn 1-x-y O2, where 0.6≤x<1.
[0017] The ternary positive electrode material is LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.94 Co 0.03 Mn 0.03 One of O2.
[0018] A coated and modified high-nickel ternary positive electrode material prepared by the above-mentioned preparation method.
[0019] A lithium-ion battery comprises a positive electrode, a negative electrode, a separator and an electrolyte. The positive electrode comprises a positive electrode collector and a positive electrode material layer arranged on the surface of the positive electrode collector. The positive electrode material layer comprises a positive electrode active substance. The positive electrode active substance is the above-mentioned coated and modified high-nickel ternary positive electrode material.
[0020] Beneficial effects:
[0021] The ternary positive electrode material prepared by the present invention has higher charge and discharge efficiency and good cycle life. Barium zirconate, as a high-quality coating material, can effectively improve the performance of the ternary positive electrode material due to its good chemical stability and superior electrochemical properties. Barium zirconate coating can significantly enhance the structural stability of the material, improve its thermal stability, and reduce the reaction with the electrolyte, thereby extending the cycle life of the battery and improving its safety. Therefore, barium zirconate coating technology has become an effective means to solve these problems and has important practical application value. Compared with some other coating methods, the sol-gel method generally has lower production costs and better scalability, and is suitable for large-scale production. The sol-gel method can form a uniform and dense barium zirconate layer on the surface of the positive electrode material, which helps to optimize the overall performance of the battery, including energy density, power density and charge and discharge efficiency. The sol-gel process parameters (such as solution concentration, reaction temperature and time) can be flexibly adjusted to achieve the optimal performance of the barium zirconate coating layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The XRD spectrum of the coated and modified high-nickel ternary positive electrode material in Example 2;
[0023] Figure 2 This is a comparison chart of the cycle performance of lithium-ion batteries made from the coated and modified high-nickel ternary positive electrode material in Example 2 and the comparative sample. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments and test examples. However, those skilled in the art should understand that the embodiments are only used to illustrate the technical solution of the present invention and should not be regarded as limiting the scope of protection of the present invention.
[0025] Unless otherwise specified, the experimental methods used in the following embodiments and experimental examples are all conventional methods; the raw materials, reagents, instruments, etc. used are all commonly used in the art, available to the public or commercially available unless otherwise specified.
[0026] Example 1
[0027] The preparation method of the coated modified high nickel ternary positive electrode material of this embodiment comprises the following steps:
[0028] 1) Nickel sulfate hexahydrate (NiSO4·6H2O), cobalt sulfate heptahydrate (CoSO4·7H2O) and manganese sulfate monohydrate (MnSO4·H2O) are weighed in a stoichiometric ratio and added to deionized water, stirred to dissolve, and then sodium hydroxide aqueous solution and ammonia water are added, and the stirring speed, temperature and pH are controlled to carry out stirring reaction to obtain a precipitate.
[0029] The resulting precipitate was filtered, and the solid was then rinsed with deionized water, dried, and then dried under vacuum at 110 °C overnight to obtain Ni 0.8 Co 0.1 Mn 0.1 (OH)2 hydroxide precursor.
[0030] 2) Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 hydroxide precursor and LiOH·H2O were weighed and mixed evenly at a molar ratio of 1:1.05, and then the mixture was preheated at 480°C for 5h in an oxygen atmosphere in a tube furnace, and then sintered at 750°C for 15h to obtain a high-nickel ternary cathode material LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811).
[0031] 3) Weigh 118.4 mg of zirconium acetate and 92.4 mg of barium acetate in a molar ratio of 1:1 and dissolve them in 50 mL of deionized water, and stir evenly.
[0032] Then, hydrochloric acid was added thereto to adjust the pH to 6, and the mixture was stirred, heated, and the temperature was controlled at 60-80° C. to form a uniform BaZrO 3 sol.
[0033] 4) Disperse 10g of NCM811 powder in the above sol, heat and stir for 4h under Ar protection atmosphere, evaporate the solution completely, and dry the obtained product in a vacuum drying oven at 90℃ for 10h. Then sinter at 500℃ for 5h in Ar atmosphere to obtain a barium zirconate coated ternary cathode material. The BZO coating concentration is 1%wt, and the sample is recorded as 1BZO-NCM.
[0034] Example 2
[0035] The preparation method of the coated modified high nickel ternary positive electrode material of this embodiment comprises the following steps:
[0036] 1) Nickel sulfate hexahydrate (NiSO4·6H2O), cobalt sulfate heptahydrate (CoSO4·7H2O) and manganese sulfate monohydrate (MnSO4·H2O) are weighed in a stoichiometric ratio and added to deionized water, stirred to dissolve, and then sodium hydroxide aqueous solution and ammonia water are added, and the stirring speed, temperature and pH are controlled to carry out stirring reaction to obtain a precipitate.
[0037] The resulting precipitate was filtered, and the solid was then rinsed with deionized water, dried, and then dried under vacuum at 110 °C overnight to obtain Ni 0.8 Co 0.1 Mn 0.1 (OH)2 hydroxide precursor.
[0038] 2) Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 hydroxide precursor and LiOH·H2O were weighed and mixed evenly at a molar ratio of 1:1.05, and then the mixture was preheated at 480°C for 5h in an oxygen atmosphere in a tube furnace, and then sintered at 750°C for 15h to obtain a high-nickel ternary cathode material LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811).
[0039] 3) Weigh 236.8 mg of zirconium acetate and 184.7 mg of barium acetate in a molar ratio of 1:1 and dissolve them in 50 mL of deionized water, and stir evenly.
[0040] Then, hydrochloric acid was added thereto to adjust the pH to 5, and the mixture was stirred, heated, and the temperature was controlled at 60-80° C. to form a uniform BaZrO 3 sol.
[0041] 4) Disperse 10g of NCM811 powder in the above sol, heat and stir for 4h under Ar protection atmosphere, evaporate the solution completely, and dry the obtained product in a vacuum drying oven at 90℃ for 10h. Then sinter at 500℃ for 5h in Ar atmosphere to obtain a barium zirconate coated ternary cathode material. The BZO coating concentration is 2%wt, and the sample is recorded as 2BZO-NCM.
[0042] Example 3
[0043] The preparation method of the coated modified high nickel ternary positive electrode material of this embodiment comprises the following steps:
[0044] 1) Nickel sulfate hexahydrate (NiSO4·6H2O), cobalt sulfate heptahydrate (CoSO4·7H2O) and manganese sulfate monohydrate (MnSO4·H2O) are weighed in a stoichiometric ratio and added to deionized water, stirred to dissolve, and then sodium hydroxide aqueous solution and ammonia water are added, and the stirring speed, temperature and pH are controlled to carry out stirring reaction to obtain a precipitate.
[0045] The resulting precipitate was filtered, and the solid was then rinsed with deionized water, dried, and then dried under vacuum at 110 °C overnight to obtain Ni 0.8 Co 0.1 Mn 0.1 (OH)2 hydroxide precursor.
[0046] 2) Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 hydroxide precursor and LiOH·H2O were weighed and mixed evenly at a molar ratio of 1:1.05, and then the mixture was preheated at 480°C for 5h in an oxygen atmosphere in a tube furnace, and then sintered at 750°C for 15h to obtain a high-nickel ternary cathode material LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811).
[0047] 3) Weigh 355.2 mg of zirconium acetate and 277.1 mg of barium acetate in a molar ratio of 1:1 and dissolve them in 50 mL of deionized water, and stir evenly.
[0048] Then, hydrochloric acid was added thereto to adjust the pH to 5, and the mixture was stirred, heated, and the temperature was controlled at 60-80° C. to form a uniform BaZrO 3 sol.
[0049] 4) Disperse 10g of NCM811 powder in the above sol, heat and stir for 4h under Ar protection atmosphere, evaporate the solution completely, and place the obtained product in a vacuum drying oven at 90℃ for 10h. Then sinter at 500℃ for 5h in Ar atmosphere to obtain a barium zirconate-coated ternary cathode material. The BZO coating concentration is 3%wt, and the sample is recorded as 3BZO-NCM.
[0050] Comparative Example
[0051] This comparative example directly uses the high-nickel ternary positive electrode material LiNi prepared in step 2) of Example 1 0.8 Co 0.1 Mn 0.1 O2 (NCM811) is used as the active material of the positive electrode material of lithium-ion batteries and is no longer coated.
[0052] Experimental example
[0053] (1) Physical and chemical testing
[0054] The 2BZO-NCM sample prepared in Example 2 was subjected to XRD test. The test results are as follows: Figure 1 shown.
[0055] from Figure 1 It can be seen that the XRD pattern of the barium zirconate coated sample is basically consistent with the hexagonal α-NaFeO2 structure of the R-3m space group. This shows that a small amount of barium zirconate coating modification will not change the original sample LiNi 0.8 Co 0.1 Mn 0.1 Crystal structure of O2 cathode material. In addition, it can be seen from the XRD diagram that the modified material has obvious split peaks between the (108) / (110) and (006) / (102) crystal planes, which means that the modified material has good crystallinity.
[0056] (2) Electrochemical performance test
[0057] The products 1BZO-NCM, 2BZO-NCM and 3BZO-NCM obtained in all the above examples were used as positive electrode active materials, and the high nickel ternary positive electrode material LiNi prepared in step 2) of Example 1 was used. 0.8 Co 0.1 Mn 0.1 O2 was used as the positive electrode active material sample of the comparative example, and was made into positive electrode sheets, with lithium sheets as negative electrodes, assembled into lithium-ion button batteries, the model of which was CR2032, and then tested.
[0058] The test conditions are: temperature is 50℃, charge and discharge voltage range is 3-4.3V, cycle test charge and discharge rate is 1C, and cycle is 100 times.
[0059] The results of the discharge specific capacity and capacity retention rate obtained by the test are shown in Table 1 below. The cycle test results of the battery corresponding to the sample of Example 2 and the comparative sample are shown in Table 1 below. Figure 2 shown.
[0060] Table 1
[0061] Experimental groups 1C discharge specific capacity (mAh / g) Cycle capacity retention rate (%) Example 1 180.8 73.7 Example 2 184.3 78.2 Example 3 182.5 74.9 Comparative Example 176.3 69.6
[0062] As can be seen from Table 1, after barium zirconate coating modification, the discharge specific capacity and cycle capacity retention rate of the battery under high temperature conditions are improved. This sol-gel method is used to coat barium zirconate on the surface of the material. The thermal barrier effect of barium zirconate hinders heat transfer and improves the thermal stability of the electrode; at the same time, barium zirconate as a coating layer effectively isolates the electrode from the electrolyte, reduces the side reaction between the electrode and the electrolyte, and enhances the interface stability.
[0063] from Figure 2It can be seen that the implementation case is significantly better than the comparison case in rate performance, which is specifically manifested in that under the same conditions, the implementation case can provide higher charge and discharge efficiency. This advantage makes the implementation case more effective in high-power applications and can meet more stringent performance requirements.
Claims
1. A method for preparing a coated modified high nickel ternary positive electrode material, characterized in that: The steps include: 1) mixing a soluble zirconium source and a soluble barium source uniformly in water, then adjusting the pH to 3-7, and stirring at 60-80° C. to obtain a sol; 2) The ternary positive electrode material is mixed evenly with the sol prepared in step 1), heated in an inert atmosphere to evaporate the solvent, vacuum dried, and then sintered at 300-900° C. for 2-6 hours to obtain the product.
2. The method for preparing the coated modified high nickel ternary positive electrode material according to claim 1, characterized in that: In step 1), the soluble zirconium source is at least one of zirconium chloride, zirconium acetate, zirconium nitrate and zirconium oxide.
3. The method for preparing the coated modified high nickel ternary positive electrode material according to claim 1, characterized in that: In step 1), the soluble barium source is at least one of barium chloride, barium acetate, barium nitrate and barium oxide.
4. The method for preparing the coated modified high nickel ternary positive electrode material according to claim 1, characterized in that: The molar ratio of the soluble zirconium source to the soluble barium source in step 1) is 1:1-3.
5. The method for preparing the coated modified high nickel ternary positive electrode material according to claim 1, characterized in that: In step 2), the temperature for heating and evaporating the solvent is 50-150° C. and the time is 6-12 hours.
6. The method for preparing the coated modified high nickel ternary positive electrode material according to claim 1, characterized in that: In step 2), the sintering temperature is 500-600° C. and the sintering time is 5-6 hours.
7. The method for preparing the coated modified high nickel ternary positive electrode material according to any one of claims 1 to 6, characterized in that: The ternary positive electrode material is prepared by a method comprising the following steps: uniformly mixing nickel sulfate, cobalt sulfate and manganese sulfate in water, adding sodium hydroxide and ammonia water, stirring for reaction, solid-liquid separation, washing, and vacuum drying for 12-24 hours to prepare a precursor; then heat treating the precursor at 450-500° C. for 4-6 hours in an oxygen atmosphere; and then sintering at 700-800° C. for 12-18 hours.
8. The method for preparing the coated modified high nickel ternary positive electrode material according to claim 7, characterized in that: The structure of the ternary cathode material can be expressed as LiNi x Co y Mn 1-x-y O2, where 0.6≤x<1.
9. A coated and modified high-nickel ternary positive electrode material prepared by the preparation method described in claim 1.
10. A lithium ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode comprises a positive electrode current collector and a positive electrode material layer disposed on the surface of the positive electrode current collector, wherein the positive electrode material layer comprises a positive electrode active material, characterized in that: The positive electrode active material is the coated and modified high-nickel ternary positive electrode material as described in claim 9.
Citation Information
Patent Citations
Preparation method of lanthanum zirconate in-situ coated high-nickel ternary cathode material
CN109461917A
Composite lithium-rich manganese-based positive electrode material and preparation method and application thereof
CN111916710A
Barium titanate coated ternary positive electrode material and preparation method and application thereof
CN115483383A
Composite coated positive electrode material as well as preparation method and application thereof
CN118619372A
Multi-element modified single-crystal positive electrode material, preparation method thereof, lithium ion battery and power utilization device
CN118943317A
Cited By
Neodymium-copper-modified high-nickel ternary positive electrode material as well as preparation method and application thereof
CN120581583A